Gender Mainstreaming towards the Mediterranean: the Case of the ENP. Issue 5 (3rd September 2017) - Giusti, Serena
Abstract: This article explores how the European Neighbourhood Policy (ENP) has supported policies promoting the improvement of women's conditions in Mediterranean countries. It points out the evolution of the European Union's gender mainstreaming in the various manifestations of its external policies directed to the region. Gender mainstreaming has been pursued through the usual practice, largely used in recent enlargements: norm diffusion. This method does not allow for a reconceptualization of the policies issued: partners only have the possibility of deciding the pace of implementation of a set of goals selected among those recommended by the EU. The 2011 wave of turmoil on the southern shores of the Mediterranean has contributed to refocusing the EU's actions on women. The new framework for Gender Equality and Women's Empowerment delivered in 2016 has established that gender equality will be mainstreamed through all the EU's external policies. Although efforts have been made to appraise it, the EU's gender strategy has mostly failed to confront the structural causes of inequality. It has mainly focused on the external aspects of the question while underestimating cultural, domestic and familial impediments and neglecting national debates or the contributions of local feminists. The EU's gender mainstreaming remains a unidirectional policy.